Educating biomedical 3D printing engineers (Transactions on Additive Manufacturing Meets Medicine, 2021)
Medical 3D printing is improving clinical care in many hospitals worldwide. Biomedical engineers are often highlighted as a key player in creating accurate and functional 3D prints from medical images that satisfy the needs of the clinicians. This requires multi-disciplinary knowledge in many different fields, including anatomy, medical imaging modalities, segmentation, Computer Aided Design (CAD) and additive manufacturing know-how. Consequently, we have begun teaching the necessary prerequisites at Aarhus University in a course focused on gaining a practical understanding of the necessary skills and technologies. In this work we present our framework for educating skilled medical 3D printing engineers.
Keywords: Medical Additive Manufacturing; Course; Education; Quality Assurance; Regulatory Requirements